Neonatal Encephalopathy Is Associated With Altered IL-8 and GM-CSF Which Correlates With Outcomes - Sweetman, Deirdre U.; Strickland, Tammy; Melo, Ashanty M.; Kelly, Lynne A.; Onwuneme, Chike; Watson, William R.; Murphy, John F. A.; Slevin, Marie; Donoghue, Veronica; O'Neill, Amanda; Molloy, Eleanor J. (Frontiers in Pediatrics, 2021)
Aim: To investigate the relationship between cytokines associated with innate immune cell activation and brain injury and outcome in infants with NE compared to neonatal controls. Methods: Serum and CSF biomarkers associated with activated neutrophils and monocytes [Interleukin-8 (IL-8) and Granulocyte-Macrophage-Colony-Stimulating-Factor (GM-CSF)] were serially measured using duplex immunoassays on day 1, 3 and 7 in term newborns with NE and controls. Results were compared to grade of encephalopathy, seizures, MRI brain imaging, mortality and Bayley Score of Infant and Toddler Development (Bayley-III) at 2 years of age. Results: Ninety-four infants had serum samples collected with 34 CSF samples. NE Grade II/III was significantly associated with elevated on day 2 serum IL-8. Mortality was best predicted by elevated day 1 IL-8. GM-CSF was initially elevated on day 1 and abnormal MRI imaging was associated with decreased day 2 GM-CSF. Elevated GM-CSF at day of life 6-7 correlated negatively with composite cognitive, language and motor Bayley-III scores at two years. Conclusion: Moderate or severe NE and mortality was associated with elevated IL-8. Day 2 GM-CSF could predict abnormal MRI results in NE and Bayley-III. Therefore, these cytokines are altered in NE and may predict early outcomes and further implicate inflammatory processes in NE.